Relaxation of selective constraint on dog mitochondrial DNA following domestication - Björnerfeldt, Susanne; Webster, Matthew T.; Vilà, Carles (Genome Research, 2006)
The domestication of dogs caused a dramatic change in their way of life compared with that of their ancestor, the gray wolf. We hypothesize that this new life style changed the selective forces that acted upon the species, which in turn had an effect on the dog’s genome. We sequenced the complete mitochondrial DNA genome in 14 dogs, six wolves, and three coyotes. Here we show that dogs have accumulated nonsynonymous changes in mitochondrial genes at a faster rate than wolves, leading to elevated levels of variation in their proteins. This suggests that a major consequence of domestication in dogs was a general relaxation of selective constraint on their mitochondrial genome. If this change also affected other parts of the dog genome, it could have facilitated the generation of novel functional genetic diversity. This diversity could thus have contributed raw material upon which artificial selection has shaped modern breeds and may therefore be an important source of the extreme phenotypic variation present in modern-day dogs.